2017
DOI: 10.1155/2017/7047909
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Is More Associated with Albuminuria than Decreased Glomerular Filtration Rate in Patients with Type 2 Diabetes Mellitus: The REBOUND Study

Abstract: Aim The aim of this study was to evaluate the association between arterial stiffness and albuminuria and glomerular filtration rate (GFR) in patients with type 2 diabetes mellitus. Methods This multicenter cohort study analyzed 2613 patients with type 2 diabetes. Brachial-ankle pulse wave velocity (baPWV) was used as a noninvasive marker of arterial stiffness. Additionally, the patients were categorized into four groups according to their albumin-to-creatinine ratio (ACR, normoalbuminuria versus albuminuria) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…In the present study of Japanese patients with type 2 diabetes, arterial stiffness as measured by the baPWV might have been associated with albuminuria and a low eGFR. This finding is consistent with the results of previously published data showing that a high baPWV was associated with both the development of albuminuria and a decline in the eGFR without albuminuria in Korean patients with type 2 diabetes. However, in this previous study, the baPWV was not identified as an independent risk factor for a decline in the eGFR without albuminuria after adjusting for significant clinical variables, such as BMI, duration of diabetes, systolic BP, pulse pressure, heart rate, smoking, alcohol consumption, HbA1c level, high‐density lipoprotein cholesterol level, C‐reactive protein level, insulin treatment and RAS inhibitor use.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study of Japanese patients with type 2 diabetes, arterial stiffness as measured by the baPWV might have been associated with albuminuria and a low eGFR. This finding is consistent with the results of previously published data showing that a high baPWV was associated with both the development of albuminuria and a decline in the eGFR without albuminuria in Korean patients with type 2 diabetes. However, in this previous study, the baPWV was not identified as an independent risk factor for a decline in the eGFR without albuminuria after adjusting for significant clinical variables, such as BMI, duration of diabetes, systolic BP, pulse pressure, heart rate, smoking, alcohol consumption, HbA1c level, high‐density lipoprotein cholesterol level, C‐reactive protein level, insulin treatment and RAS inhibitor use.…”
Section: Discussionsupporting
confidence: 92%
“…The REBOUND study is a multicenter prospective observational study to assess the association between baPWV and CVD in patients with type 2 diabetes. A detailed description of the design has been published previously [ 18 , 19 ]. Briefly, the REBOUND study was conducted at eight general and teaching hospitals in Busan, Korea.…”
Section: Methodsmentioning
confidence: 99%
“…Albuminuria is also a prognostic marker for cardiovascular disease, and hospitalization rates increases with albuminuria in all eGFR ranges [34]. In diabetic individuals, arterial stiffness is more associated with albuminuria than with a decrease in eGFR [35], and the association is also observed in the HN range [36]. Previous findings correlate urinary ACR with subclinical atherosclerosis and cardiovascular risk [14,37].…”
Section: Discussionmentioning
confidence: 96%
“…Within inflammation, three different categories are upregulated in HN individuals: 'negative acute phase response' containing eight proteins and showing a variation rate (DZc) of 7.91; 'IL-12 signaling and production in macrophages' including 32 proteins and DZc ¼ 6.28; and 'serine protease inhibitor' category, composed by 35 Early damage in normoalbuminuria…”
Section: Coordinated Response Analysis Reveals Altered Biological Pro...mentioning
confidence: 99%